2022
DOI: 10.1007/s00429-021-02433-2
|View full text |Cite
|
Sign up to set email alerts
|

Amateur singing benefits speech perception in aging under certain conditions of practice: behavioural and neurobiological mechanisms

Abstract: Limited evidence has shown that practising musical activities in aging, such as choral singing, could lessen age-related speech perception in noise (SPiN) di culties. However, the robustness and underlying mechanism of action of this phenomenon remain unclear. In this study, we used surface-based morphometry combined with a moderated mediation analytic approach to examine whether singing-related plasticity in auditory and dorsal speech stream regions can mitigate age-related SPiN di culties. 36 choral singers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 93 publications
(106 reference statements)
1
9
0
Order By: Relevance
“…This study demonstrates that long-term musicianship mitigates age-related deficits in audiovisual speech-in-noise perception through both functional preservation and compensation. In line with and extending previous studies using audio-only speech stimuli ( 8 10 , 12 , 39 ), we found that lifelong music playing lessens age-related declines in audiovisual speech-in-noise perception. OM showed equivalent phoneme representations in visual and sensorimotor regions to that of YNM, while the phoneme representations in these regions in the ONM were dedifferentiated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study demonstrates that long-term musicianship mitigates age-related deficits in audiovisual speech-in-noise perception through both functional preservation and compensation. In line with and extending previous studies using audio-only speech stimuli ( 8 10 , 12 , 39 ), we found that lifelong music playing lessens age-related declines in audiovisual speech-in-noise perception. OM showed equivalent phoneme representations in visual and sensorimotor regions to that of YNM, while the phoneme representations in these regions in the ONM were dedifferentiated.…”
Section: Discussionsupporting
confidence: 91%
“…Among age-related cognitive deficits, difficulty in understanding speech in noisy environments is one of the most prevalent, even in older adults who show normal hearing for their age. Although musicians' advantage in speech perception in noise is not robust in young and middle-aged adults (5)(6)(7), accruing evidence suggests that age-related decline in speech-in-noise perception can be mitigated by long-term or short-term musical training (8)(9)(10)(11)(12). However, such benefits have not yet been demonstrated in audiovisual speechin-noise scenarios in aging populations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MIT, a singing-based intervention for treating nonfluent aphasia, has been shown to improve connected speech, naming, and repetition ( Sparks et al, 1974 ; Van Der Meulen et al, 2014 ; Zumbansen et al, 2014 ) and linking the positive effects to temporal and frontal speech motor areas, either in the left ( Belin et al, 1996 ; Breier et al, 2011 ) or right ( Schlaug et al, 2008 ; Wan et al, 2014 ; Tabei et al, 2016 ) hemisphere. In the healthy older adults, regular singing has recently been linked to enhanced executive function ( Pentikäinen et al, 2021 ; Vetere et al, 2024 ), frontotemporal auditory functioning ( Pentikäinen et al, 2022 ), structural connectivity ( Perron et al, 2021 ), and structural plasticity in auditory and dorsal speech regions ( Perron et al, 2022 ), suggesting that it may have neuroprotective effects in aging.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that group singing is effective for promoting long‐term quality of life, mood, cognitive function, and social engagement (Coulton et al, 2015 ; Johnson et al, 2020 ; Pentikäinen et al, 2021 ; Skingley et al, 2016 ; see also Cohen et al, 2006 ), thus providing a cost‐effective tool to support mental health in the ageing population (Coulton et al, 2015 ). Despite its great potential for promoting brain health across adult life, very few studies (e.g., Perron et al, 2021 , 2022 ) have yet studied the effects of choir singing on the ageing brain. Direct evidence of whether choir singing might support the preservation of healthy brain structure at whole‐brain scale is currently missing.…”
Section: Introductionmentioning
confidence: 99%